Isoimperatorin exerts anti-inflammatory activity by targeting the LPS-TLR4/MD-2-NF-κB pathway. (March 2021) - Chen, Guirong; Liu, Yunong; Xu, Yubin; Zhang, Mingbo; Guo, Song; Zhang, Gang
Isoimperatorin (QHS) is a phytoconstituent found in the methanolic extracts obtained from the roots of Angelica dahurica, which contains anti-inflammatory, anti-bacterial, analgesic, anti-tumor, and vasodilatory activities. QHS possesses potent antagonistic activity against lipopolysaccharide (LPS)-induced inflammation; however, the mechanism of action remains unclear. In this study, we investigated the anti-inflammatory effect of QHS and explored the underlying mechanisms. The QHS was purchased from Jiangsu Yongjian Pharmaceutical Co., Ltd. (Jiangsu, China). We performed MTT assay, real-time PCR, ELISA, and western blotting experiments to assess the anti-inflammatory activity and the possible mechanism of QHS in vitro. Molecular docking was performed to study the binding of QHS and myeloid differentiation protein-2 (MD-2) and elucidate the possible anti-inflammatory mechanism. QHS had no significant effect on cell viability. Moreover, pre-treatment with QHS significantly decreased the release of inflammatory cytokines and mediators including NO, TNF-α, IL-6, and IL-1β. In addition, real-time PCR showed that QHS decreased the mRNA expressions of iNOS, COX-2 TNF-α, IL-6, and IL-1β. Western blotting indicated that QHS could inhibit the expression of the proteins associated with the LPS-TLR4/MD-2-NF-κB signaling pathway. Lastly, molecular docking revealed a possible binding mechanism between QHS and MD-2. QHS exhibited anti-inflammatory activity when combined with MD-2, regulating the LPS-TLR4/MD-2-NF-κB signaling pathway, and inhibiting the release and expression of inflammatory cytokines and mediators. Furthermore, QHS can be used as a potential TLR4 antagonist, which blocks MD-2 binding, for treating inflammatory responses induced by LPS.